Spatio-Temporal Modelling of Noise Pollution - Napi N.N.L.M.; Zainal M.H.; Abdullah S.; Dom N.C.; Mansor A.A.; Ahmed A.N.; Ismail M. (Penerbit UTHM, 2023)
An undesired or hazardous outdoor sound produced by human activities is referred to as environmental noise. For example, the noise emitted through industrial activities and transportation networks such as road, rail and air traffic. In Malaysia, most of the schools located very close to the roadside and near busy places such as cities, shops, and residential areas. This study aims to analyze the environmental noise in terms of spatial and temporal analysis in two primary schools in Terengganu State. The noise monitoring had conducted in two (2) primary schools with different land use; residential area (Batu Rakit Primary School) and commercial area (Paya Bunga Primary School) on the school and non-school days by using Sound Level Meter (SLM). The spatial mapping had constructed by using SketchUp 2018 and Surfer version 11 software. The noise level between both study areas was significantly different based on a p-value of less than 0.05. It also surpassed the Department of Environment (DOE) of Malaysia's permitted limit, with the Equivalent Noise Level (LAeq) in residential areas being greater than in commercial areas due to traffic volume and noise from nearby activities. Lastly, the area near the roadside has higher critical noise pollution compared with the location that furthers from the roadside. In conclusion, this study is useful in creating awareness to the public about the noise pollution effect on primary school students and is also can be used for mitigation measures to have a better place for students to study. Universiti Tun Hussein Onn Malaysia Publishers Office